Legal Study of Divorce Lawsuit Mechanism Against Absent Husband According to Indonesian Marriage Law - Natigor Daulay, R. Fahmi; Evangelista, Beverly (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Divorce lawsuit against absent husband is a legal remedy for wives abandoned by their husbands without clear residence information. This research analyzes the legal mechanism of divorce lawsuits against absent husbands based on Law No. 1 of 1974 on Marriage and Islamic Law Compilation. The research method uses normative juridical approach with secondary data of descriptive nature. Results show that absent husband divorce procedures are regulated in Article 20 paragraph (2) of Government Regulation No. 9 of 1975 and Article 138 of Islamic Law Compilation, with summons through announcements on court bulletin boards and mass media. Implementation follows ordinary divorce lawsuit procedures with additional requirements including village certificate stating the unclear domicile of the defendant.